Kewarganegaraan Ganda dalam Perspektif Hukum Positif dan Hukum Islam: Analisis Normatif-Komparatif - Azahra Zakiyatu Salamah; Clarissa Soffi’ Otama; Ratna Yulaika Dwi Yulianti; Talita Syahda Azalia Ramadhani; Syifa Aulia Putri Pramesti (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The phenomenon of dual citizenship has become increasingly significant in the era of globalization, where human mobility across borders is rising and international relations are becoming more interconnected. This study seeks to examine dual citizenship from the perspective of Indonesian positive law and Islamic law using a normative-comparative approach. Under Indonesian positive law, citizenship is governed by Law No. 12 of 2006, which essentially upholds the principle of single citizenship, with limited exceptions granted to children born from mixed marriages. In contrast, within Islamic law, citizenship is understood not merely as a legal status but also as a moral and social relationship grounded in the principles of justice, public welfare (maslahah), and the protection of human rights, as reflected in the maqasid al-shariah. The findings indicate that although differences in principle exist between Indonesian positive law and Islamic law, both share a common objective—to preserve the unity of the state and promote the well-being of its people. Therefore, harmonization between these two legal systems is essential through a dialogical and inclusive approach, ensuring that dual citizenship policies are implemented fairly, effectively, and in alignment with the socio-cultural values of Indonesian society.